2021
DOI: 10.1016/j.jaccas.2021.02.015
|View full text |Cite
|
Sign up to set email alerts
|

Extracardiac Accumulation of Technetium-99m-Pyrophosphate in Transthyretin Cardiac Amyloidosis

Abstract: This report presents a rare case of acute decompensated heart failure with technetium-99m-pyrophosphate accumulation in extracardiac sites, such as chest and abdominal walls, in addition to intense myocardial uptake of the tracer. Subsequently, an abdominal fat pad fine-needle aspiration biopsy, which provided positive findings for transthyretin amyloidosis, was performed. ( Level of Difficulty: Advanced. )

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…Few studies have investigated the usefulness of a skeletal muscle biopsy for confirming ATTR deposition in patients with ATTRwt-CA ( 22 ). We previously reported that the extracardiac 99m Tc-PYP uptake detected in patients with ATTRwt-CA indicated amyloid deposition ( 2 - 4 ). A 99m Tc-PYP imaging-based CT-guided core needle biopsy of the internal oblique muscle with a tracer uptake in patients with ATTRwt-CA has a high ATTR detection rate (88.9%), although tracer accumulation-negative patients have not been investigated ( 5 ).…”
Section: Discussionmentioning
confidence: 98%
“…Few studies have investigated the usefulness of a skeletal muscle biopsy for confirming ATTR deposition in patients with ATTRwt-CA ( 22 ). We previously reported that the extracardiac 99m Tc-PYP uptake detected in patients with ATTRwt-CA indicated amyloid deposition ( 2 - 4 ). A 99m Tc-PYP imaging-based CT-guided core needle biopsy of the internal oblique muscle with a tracer uptake in patients with ATTRwt-CA has a high ATTR detection rate (88.9%), although tracer accumulation-negative patients have not been investigated ( 5 ).…”
Section: Discussionmentioning
confidence: 98%
“…As for 99m Tc-PYP, Takahashi et al documented a case of acute decompensated heart failure where 99m Tc-PYP concentrated not only in the myocardium but also in extracardiac areas such as the thoracic and abdominal walls, confirmed by a positive fine-needle aspiration biopsy for ATTR amyloidosis [ 19 ]. While another study noted that extracardiac uptake of 99m Tc-PYP in heart failure was infrequent and seldom necessitated further investigation, it lacked specific data on cardiac amyloidosis, precluding any comparative analysis of uptake levels between patients with and without cardiac amyloidosis [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, chest- and abdomen-centered scans provide additional information. The extracardiac uptake of 99m Tc-PYP indicates the presence of amyloid deposits, which can guide the selection of a biopsy site 7,12,13 . Hutt et al 22 reported the usefulness of skeletal muscle biopsies in ATTR-CA, although these results were not described in detail.…”
Section: Discussionmentioning
confidence: 99%
“…The extracardiac uptake of 99m Tc-PYP indicates the presence of amyloid deposits, which can guide the selection of a biopsy site. 7,12,13 Hutt et al 22 reported the usefulness of skeletal muscle biopsies in ATTR-CA, although these results were not described in detail. Screening biopsies minimize the requirement for high-risk and more invasive target organ biopsies, such as endomyocardial biopsy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation